MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN SiMaYang MATERI KELARUTAN DAN HASIL KALI KELARUTAN (Ksp) - Amalia Fitri (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2016)
Abstract. A research on the use of the learning model SiMaYang on material solubility and solubility product (Ksp) at SMA Negeri 9 Banjarmasin. This study aims to determine (1) the activities of teachers, (2) the activity of students, (3) improving student learning outcomes, and (4) the students' responses. The study design was a classroom action research (PTK) with two cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects were students of class XI IPA 3 SMA Negeri 9 Banjarmasin by the number of students 32 people. Data were collected through observation, cognitive achievement test and questionnaire. Data were analyzed by using descriptive analysis of quantitative and qualitative analysis. The results showed that (1) the activities of teachers from the category quite well in the first cycle increased to both categories at the second cycle, (2) Activity student of categories is quite active in the first cycle increased to a category active in the second cycle, (3) the cognitive learning students of the percentage of 53.57% in the first cycle increased to 90.625% in the second cycle, affective learning outcomes of the category quite well in the first cycle increased to both categories at the second cycle, psychomotor learning outcomes of the category enough in the first cycle increased to the skilled category the second cycle, (4) students showed a positive response.Keywords: Learning Outcomes, Multiple Representations, models SiMaYang, solubility and solubility product (Ksp)